Comparison of the multi-configuration, time-dependent Hartree (MCTDH) method with the Arthurs and Dalgarno coupled-channel method for rotationally inelastic scattering - Malenda, Ruth; Gatti, F.; Meyer, Hans-Dieter; Talbi, D.; Hickman, A. P. (Chemical physics letters, 2013)
Calculations of rotationally inelastic scattering at thermal energies for a model atom-diatom system have been performed using two completely different methodologies. The first method is the multi-configuration time-dependent Hartree (MCTDH) wave packet method, and the second is the well known, time-independent, Arthurs and Dalgarno coupled channel formalism. Excellent agreement is obtained between the two calculations. The advantages and drawbacks of these two methods are somewhat complementary, so that the decision to use one or the other approach will depend on what type of computational results are desired.